US SEC approves sweeping amendments to rules governing money market funds. Issue 1 (5th May 2015) - Murphy, Jack; Cohen, Stephen; Carroll, Brenden; Smith, Aline A.; Virag, Matthew; Goldberg, Justin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – To explain the background and details and to discuss the implications of the USA Securities and Exchange Commission's (SEC's) July 23, 2014 amendments to Rule 2a-7 and other rules that govern money market funds under the Investment Company Act of 1940. Design/methodology/approach – Explains the background, including problems during the financial crisis, the USA Treasury's temporary guarantee program in 2008, earlier SEC proposals, and the USA Financial Stability Oversight Council's recommendations. Details the amendments to Rule 2a-7, including the authorization to impose liquidity fees and redemption gates, the floating net asset value (NAV) requirement, the impact of the amendments on unregistered money funds operating under Rule 12d1-1, guidance on fund valuation methods, disclosure requirements, requirements for money fund portfolios to be diversified as to issuers of securities and guarantors, stress testing requirements, and compliance dates. Findings – The Amendments set forth sweeping changes to money fund regulation and will have a profound effect on the money fund industry. Although the most significant provisions of the Amendments – the floating NAV requirement and the imposition of liquidity fees and redemption gates – will not go into effect for two years, the changes to the industry will be apparent almost immediately. Practical implications – Money fund managers and boards of directors should begin assessing the potential impact of the Amendments and develop a schedule to come into compliance. Originality/value – Practical guidance from experienced financial services lawyers.